Supporting field study with personalized project spaces in a geographical digital library - Lim, Ee Peng (2009)
Digital libraries have been rather successful in supporting learning activities by providing learners with access to information and knowledge. However, this level of support is passive to learners and interactive and collaborative learning cannot be easily achieved. In this paper, we study how digital libraries could be extended to serve a more active role in collaborative learning activities. We focus on developing new services to support a common type of learning activity, field study, in a geospatial context. We propose the concept of personal project space that allows individuals to work in their personalized environment with a mix of private and public data and at the same time share part of the data with team members. To support the portability of the resources in our digital library, the selected resources can be exported in an organized manner.